Global survey of serological evidence of caprine arthritis-encephalitis virus infection - Adams, D S; Oliver, R E; Ameghino, E; DeMartini, J C; Verwoerd, D W; Houwers, D J; Waghela, S; Gorham, J R; Hyllseth, B; Dawson, M (Veterinary record, 1984)
Using caprine arthritis-encephalitis virus antigen in the agar gel immunodiffusion test, 3729 serum samples from goats in over 112 locations around the world were tested for precipitating antibodies. Over 90 per cent of the 1265 positive samples came from Canada, France, Norway, Switzerland and the USA, all of which had 65 per cent reactors or greater. Fiji, Great Britain, Kenya, Mexico, New Zealand and Peru had fewer than 10 per cent positive samples; the majority of these could be traced to importations of goats from countries where there was a high occurrence of precipitating antibody. Somalia, Sudan and South Africa had no reactors among 306 samples. No reactors were found among 1116 samples from domestic and indigenous goats which were known to have had no contact with imported goats from countries which had a high occurrence.